Examining the Key Factors that Drives Live Stream Shopping Behavior - Sudaporn Sawmong (Ital Publication, 2022)
The purpose of this research was to examine the key factors that drive live-stream shopping behavior in Thailand. The specific objective was to determine the live stream shopping factors that influence purchase intention. The study was driven by the increasing role of e-commerce and live streaming shopping trends through social media marketing. For marketers, live-stream shopping is considered a valuable marketing strategy for commercial businesses to enhance sales, save expenses, and create unique marketing impacts. The study adopted the Uses and Gratification Theory and the Source Credibility Theory. Through these theories, the variables of the study were considered to be entertainment, informativeness, attractiveness, expertise, trustworthiness, culture, and purchase intention. A quantitative research methodology was adopted, with primary data collected from 370 respondents. The model was evaluated using reliability, validity, and CFA. SEM was used to analyse the hypotheses using AMOS and SPSS software. The results of the study indicated that four factors (entertainment, informativeness, expertise, and trustworthiness) have a significant and positive effect on purchase intention. Trustworthiness and entertainment had the highest effect. Attractiveness was found not to influence purchase intention, while culture did not moderate the effect of any variable on purchase intention. The research recommended that live streaming should be trustworthy in terms of sincerity, non-exaggeration, correct information, correct thoughts, and opinions. They should also be entertaining to establish positive interconnectivity between the user and the product or service, and also informative to contribute towards awareness of a product/service and offer insights that influence perceptions and behavioral intentions. Doi: 10.28991/ESJ-2022-06-06-011 Full Text: PDF